Forensic determination of drug tablets upon external exposures - Sufri, Noorshuhaida Muhamad (2020)
Pharmaceutical tablet is a prescription dosage type that includes the active component of the medication material with the suitable diluents. Exposure of drugs to environmental factors, such as moisture, heat and stress, might deteriorate the product as well as change the physicochemical properties of the drug. Such changes might also influence the safety and effectiveness of the medication tablet. This study was aimed to investigate the effect of environmental exposure on drug tablets. In this study, the samples were insulted with different condition and contaminants including closed, temperature, water, acid, base and oil. The samples were then exposed for the duration one week and one month. After the exposure duration end, physical examination was conducted to examine the physical changes that occur to the tablets. Samples profiles were generated through attenuated total reflectance-Fourier transform infrared spectroscopy (ATR-FTIR) analysis. The ATR-FTIR data was also decomposed by Principal Component Analysis (PCA) to distinguish the drug tablet samples based on the environmental exposures. Although subjected to environmental exposures, the ATR-FTIR profiles appeared very similar among the samples, as paracetamol is the main ingredient of the tablet. Since PCA did not showed significant discrimination with different environmental exposure, Discrimination Analysis (DA) was conducted to create better visualization and differentiation among the samples. DA results demonstrated that Panadol for Children and Panadol Soluble had achieved 100% correctly clustering. Additionally, Panadol-650 had reached up to 88.9% accurate classification. Other samples including Paracil (SM), Paracil (Mal), Panadol Menstrual, Uphamol-650 and Febricol-RX were hardly to be distinguished. In conclusion, physical observation was more suited in discrimination of tableted drug as compared to chemical analysis. External insults were found not to introduce any impact in the physical and chemical characteristics on the drugs tested in this study.